TWO NEW NON-HAPTOTYPIC PALYNOMORPH TAXA FROM THE MIDDLE PERMIAN UPPER GHARIF MEMBER, OMAN - MICHAEL H. STEPHENSON (Rivista Italiana di Paleontologia e Stratigrafia, 2011)
Two non-haptotypic palynomorph taxa, Schizosporis? pennyi n. sp. and Tetraporina forbesii n. sp., are described and illustrated from Subunit B of the Upper Gharif Member immediately underlying the base of the Khuff Formation at the northern Huqf outcrop, Oman. Tetraporina forbesii also occurs in heterolithic beds within the lowest part of the Khuff Formation in the Barik-36 oil well. The forms are assigned to the Wordian-Capitanian Oman and Saudi Arabia Palynological Biozone 6 (OSPZ6) on the basis of their occurrence with Florinites? balmei, and other taxa characteristic of OSPZ6. They were previously assigned to informal taxa and are likely freshwater zygospores, and their prevalence in the Subunit B section of the Upper Gharif Member may indicate impermanent stagnant ponds in a coastal plain or estuarine palaeoenvironment.